A Systematic Evaluation of Design Freedoms and Restrictions of Lattice Structures Used as Interlock Bonds - Raphael Freund; Karl Hilbig; Thomas Vietor (Designs)
Additive manufacturing provides new possibilities in product design compared to traditional manufacturing processes. Particularly additive material extrusion offers the freedom to combine multiple materials in a single component without additional steps. However, combining multiple materials often leads to reduced adhesion, which can hinder the creation of high-strength designs. This issue can be largely mitigated using the geometric freedom of additive manufacturing to produce interlocking structures. This publication investigates the use of lattice structures as interlocking bonds in multi-material applications. The aim is to aid the design of suitable lattice structures by collecting geometric freedoms of lattices, application requirements, and manufacturing constraints, for this information to be used in suitable designs in the future. Initially, the general design freedoms of lattice structures are compiled and explained. Subsequently, these design freedoms are narrowed down based on the specific requirements for interlocking bonds and the limitations imposed by geometry and material combinations during manufacturing. The publication concludes with design recommendations that can be used as the basis for interlock bonds. Suitable lattice designs should aim for high interconnectivity, interconnected porosity, and a high number of similar strut structures, all the while maintaining low dimensions in the interface direction.